2020
DOI: 10.1039/d0gc01500h
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity switch in the aerobic oxygenation of sulfides photocatalysed by visible-light-responsive decavanadate

Abstract: Selective oxygenation of sulfides to sulfones and sulfoxides was demonstrated by photocatalysis of decavanadate using O2 in methyl ethyl ketone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 84 publications
1
48
1
1
Order By: Relevance
“…Purification of reaction products was carried out by flash chromatography on silica gel (300~400 mesh, Huanghai Chemical Co. Ltd.). 1 H NMR spectra were recorded at 500 MHz, 13 C NMR spectra were recorded at 125 MHz, and in CDCl3 (containing 0.03% TMS) solutions. 1 H NMR spectra were recorded with Me4Si (δ = 0.00) as the internal reference and 13 C NMR spectra were recorded with CDCl3 (δ = 77.00) as the internal reference.…”
Section: Scheme 3 Proposed Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Purification of reaction products was carried out by flash chromatography on silica gel (300~400 mesh, Huanghai Chemical Co. Ltd.). 1 H NMR spectra were recorded at 500 MHz, 13 C NMR spectra were recorded at 125 MHz, and in CDCl3 (containing 0.03% TMS) solutions. 1 H NMR spectra were recorded with Me4Si (δ = 0.00) as the internal reference and 13 C NMR spectra were recorded with CDCl3 (δ = 77.00) as the internal reference.…”
Section: Scheme 3 Proposed Reaction Mechanismmentioning
confidence: 99%
“…Subsequently, it was further demonstrated that a CF3SO2Na-catalyzed photocatalytic method can be used for the switchable synthesis of sulfoxides and sulfones. 12b In addition, the distinctive systems, such as tetraphenylphosp-honium decavanadate/O2, 13 Polyoxomolybdate-Calix[4]arene Hybrid/H2O2 14 (Scheme 1, e), peroxomolybdenum(VI)/H2O2, 15 WO3 Nanoparticles/H2O2, 16 electrochemical system, 17 et al, 18 were also adopted for the switchable oxidation of sulfides. Despite the remarkable achievements as mentioned above, the high reaction temperature, commercially unavailable catalyst or unique experimental equipment were often indispensable, and O-source of these switchable oxidation reactions focuses mainly on H2O2, O2, TBHP and Oxone.…”
mentioning
confidence: 99%
“…POVs, that represent a sub-class of the polyoxometalates (POMs), are anionic molecular oxides exhibiting a rich structural chemistry due to the ability of the vanadium to adopt different oxidation states (V IV [1,2]. The growing interest for POVs is mainly due to their striking redox and catalytic properties making POVs particularly appealing for both fundamental and applied studies related to the redox-flow batteries [3][4][5][6], the lithium or sodiumion batteries [7][8][9][10], the water oxidation catalysis [11,12] or photocatalysis [13]. Recently, it was also demonstrated that POVs constitute also excellent models to study the intriguing properties of vanadium solid-state oxides [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…2-, isolated as tetra-n-butylammonium (TBA + ) salt has been characterized by singlecrystal X-ray diffraction, infrared, UV-vis and multinuclear NMR ( 1 H, 13 C and 51 V) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…[6] 2019 年华东师范大学姜雪峰 [7] 实现了可见光诱导铀盐催化硫 醚的选择性氧合反应(Scheme 1, c). 最近, 东京大学 Suzuki 和 Yamaguchi 等 [8] 报道了可见光诱导四苯基膦十…”
unclassified